2016
DOI: 10.1016/j.cub.2016.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Representation of Numerosity Zero in the Primate Parieto-Frontal Number Network

Abstract: Neurons in the primate parieto-frontal network represent the number of visual items in a collection, but it is unknown whether this system encodes empty sets as conveying null quantity. We recorded from the ventral intraparietal area (VIP) and the prefrontal cortex (PFC) of monkeys performing a matching task including empty sets and countable numerosities as stimuli. VIP neurons encoded empty sets predominantly as a distinct category from numerosities. In contrast, PFC neurons represented empty sets more simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 48 publications
(75 reference statements)
14
65
0
Order By: Relevance
“…Successive integration, if any, may therefore sharpen frontal numerosity representations. These are more closely linked to behavioural performance 40,41 , so finer tuning widths here may improve behavioural performance. Alternatively, multiple numerosity maps may instead aid interactions with multiple perceptual and cognitive systems without successive integrations Sensory and motor topographic maps are typically grouped in specific regions, allowing interactions over minimal distances.…”
Section: Lettersmentioning
confidence: 99%
“…Successive integration, if any, may therefore sharpen frontal numerosity representations. These are more closely linked to behavioural performance 40,41 , so finer tuning widths here may improve behavioural performance. Alternatively, multiple numerosity maps may instead aid interactions with multiple perceptual and cognitive systems without successive integrations Sensory and motor topographic maps are typically grouped in specific regions, allowing interactions over minimal distances.…”
Section: Lettersmentioning
confidence: 99%
“…This is what the study by RamirezCardenas and colleagues directly investigated [9]. They found differential tuning for empty sets between parietal and frontal areas.…”
mentioning
confidence: 52%
“…A recent paper by Ramirez-Cardenas and colleagues [9] provides striking evidence favoring this proposal. The authors investigated whether single neurons and neuronal populations in the primate parietofrontal magnitude system, which typically encode the number of visual stimuli in a set, also encode empty sets conveying a null quantitative value.…”
mentioning
confidence: 96%
“…It is also possible that even if zero is stored by the ANS, it requires additional supporting processes. For example, it was found that monkeys could solve number matching task with empty set, and cells tuned to the empty sets were found both in the ventral intraparietal area and in the prefrontal cortex, as it has been observed for positive numbers (Ramirez-Cardenas, Moskaleva, & Nieder, 2016). However, 3 only the cells in the prefrontal cortex showed the distance effect for zero, a sign of ANS processing, and not the intraparietal cells, although the ANS is supposed to be localized in the intraparietal area (Dehaene, Piazza, Pinel, & Cohen, 2003).…”
Section: Lack Of Developmental Models Of Understanding Zeromentioning
confidence: 99%
“…The most frequently referred model suggests that semantic numerical processing is driven by the approximate number system that represents numbers in an imprecise way (Feigenson et al, 2004;Merritt & Brannon, 2013;Moyer & Landauer, 1967). This system might include zero, although this ability can be debated (Dakin et al, 2011;Dehaene et al, 1993;Merritt & Brannon, 2013;Ramirez-Cardenas et al, 2016). It is possible that while the positive numbers and in some cases the zero value could be handled by this system (as in the comparison task), in some other cases the zero value should be handled by another system (as in the number status of zero task).…”
Section: The Dual Nature Of Zeromentioning
confidence: 99%